High prevalence and risk factors associated with latent tuberculous infection in two Colombian prisons (2014)
ABSTRACT : Setting: Two prisons in Medellín and Itagüí, Colombia. Objective: To determine the prevalence of tuberculin skin test (TST) positivity in prisoners and the annual risk of tuberculous infection (ARTI), to identify risk factors associated with a positive result, and to describe progression to active disease. Design: Cross-sectional study. Inmates were included if time of incarceration was ⩾1 year and excluded if subjects had had previous or active tuberculosis (TB), or conditions that could hamper TST administration or interpretation. Results: We screened 1014 inmates. The overall prevalence of TST positivity was 77.6%. The first TST administration resulted in 66% positivity, and the second TST an additional 11.6%. In Prison One, the ARTI was 5.09% in high TB incidence cell blocks and 2.72% in low TB incidence blocks. In Prison Two, the ARTI was 2.77%. Risk factors associated with TST positivity were history of previous incarceration and length of incarceration. Among all those included in the study, four individuals developed active pulmonary TB. Conclusion: Prevalence of TST positivity in prisoners and the ARTI were higher than in the general population, but differed between prisons; it is important to apply a second TST to avoid an overestimation of converters during follow-up.